2003
DOI: 10.1001/archinte.163.16.1905
|View full text |Cite
|
Sign up to set email alerts
|

Role of Environmental Contamination as a Risk Factor for Acquisition of Vancomycin-Resistant Enterococci in Patients Treated in a Medical Intensive Care Unit

Abstract: Among all other factors associated with VRE transmission, VRE acquisition may depend on room contamination, even after extensive cleaning. This study underscores the need for better cleaning and the role of the environment in transmission of VRE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
119
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(127 citation statements)
references
References 59 publications
1
119
0
7
Order By: Relevance
“…The study by Martinez et al showed significant relationship between antibiotic usage (vancomycin, cephalosporin, metronidazole and quinolones) and emergence of VRE (28).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Martinez et al showed significant relationship between antibiotic usage (vancomycin, cephalosporin, metronidazole and quinolones) and emergence of VRE (28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the capacity of enterococci to survive outside the human body for prolonged periods of time contributes to cross-contamination through the hands of healthcare workers, leading to outbreaks [1,2]. The hospital environment can be a reservoir of resistant bacteria, and the role of a possible dissemination of these bacteria, especially vancomycin-resistant enterococci (VRE) via inanimate surfaces and equipment, has been documented by several researchers [3][4][5][6]. Moreover, the cross-transmission, between patients via contaminated hands and surfaces, of multidrug-resistant microorganisms increases length of stays in hospitals, healthcare costs, and mortality [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…High acquisition and environmental contamination rates and survival characteristics of E. faecium that may increase the risk for acquisition of this opportunistic pathogen in hospital settings have previously been described [3,6,7]. In a previous study, we have found extensive in vitro survival of VREfm for approximately 4 years [8].…”
Section: Introductionmentioning
confidence: 69%
“…This means that this bacterium can re-emerge from hidden places in a presumed 'AREfm-free ward' by colonising susceptible patients. This stresses the importance of adequate environmental decontamination of patient rooms to break the chain of patient-to-patient cross-transmission of multidrugresistant nosocomial pathogens [6].…”
Section: Discussionmentioning
confidence: 99%